Plataforma de gerenciamento de cisternas open hardware e open source - Surkamp, Christian Whelinton (2015)
Reuse of water is becoming more attractive and necessary nowadays due to several factors such as the cost and the increasing difficulty to achieving it. Considering this necessity, the focus of this work is to develop a platform for managing cisterns to monitor and optimize rainwater reuse. To develop the platform it was used some technologies such as PHP, HTML5, and MySQL to process, display, and store data. The data was collected with the help of a free hardware electronics prototyping platform (Arduino) and sensors for water level, processing and storing them in a SQL database. Thus, the goal wass to generate potable water savings, also looking for financial savings by reducing the water consumption from water utilities.